2023
DOI: 10.1108/caer-12-2021-0244
|View full text |Cite
|
Sign up to set email alerts
|

What determines the development of a rural collective economy? A fuzzy set qualitative comparative analysis (fsQCA) approach

Abstract: PurposeThis study explores configurations that promote the development of collective economies in China's rural villages and reveals the multiple development pathways that otherwise remain relatively unexamined in the literature.Design/methodology/approachThe authors obtained first-hand representative case data from 20 villages in 12 counties in 5 provinces in East, West and Central China via fieldwork and applied fuzzy set qualitative comparative analysis (fsQCA) to conduct a configurational comparative study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 28 publications
0
1
0
Order By: Relevance
“…It aligns with the current mainstream rural development theory used in developed European countries [52]. This study incorporates both existing research findings and current realities [53][54][55]. The stable development of the rural collective economy requires a combination of internal and external resources, including (1) human resources, (2) financial resources, (3) institutional supply, (4) technical conditions, and (5) natural resources.…”
Section: (4) Constructing the Mimics Modelmentioning
confidence: 65%
“…It aligns with the current mainstream rural development theory used in developed European countries [52]. This study incorporates both existing research findings and current realities [53][54][55]. The stable development of the rural collective economy requires a combination of internal and external resources, including (1) human resources, (2) financial resources, (3) institutional supply, (4) technical conditions, and (5) natural resources.…”
Section: (4) Constructing the Mimics Modelmentioning
confidence: 65%
“…Social Development Level: This factor mainly encompasses the degree of attracting immigrants and the level of aging ( 43 ). Hence, the economic development level is calculated by weighing two relative indicators: net migration rate (50%) and older adult dependency ratio (50%).…”
Section: Research Methodology and Datamentioning
confidence: 99%
“…The progress of China's rural collective economy can be divided into three stages (Deng et al, 2023), as shown in Figure 1. Prior to the reform and opening up, China's rural areas had established a traditional collective organization based on the communalization, which experienced a phase of rapid development (Hong et al, 2023). Following the Third Plenary Session of the 11th Central Committee in 1978, the rural reform resulted in the collapse of the people's commune and the gradual establishment of the family contract responsibility system, which put the enhancement of the collective economy in a dormant state (Zhang et al, 2019).…”
Section: Introductionmentioning
confidence: 99%